حِجَاجِيَّة المَثَل عِندَ أكثَم بنِ صَيفِي دراسة تحليلية - بدر بن علي, العبد القادر (Revues faculté des lettres et des langues, 2017)
ملخــــــص:      يناقش هذا البحث حِجَاجِيَّة المثل عند أكثم بن صيفي من خلال تقسيمه إلى مطلبين: المطلب الأول: ويحتوي على المهاد النظري للبحث، والمطلب الثاني: ويشتمل على دراسة تطبيقية على حِجَاجِيَّة الـمَثل عِندَ أكثَم بنِ صَيفِي بعد تقسيمه إلى أنواع هي: المثل السائر، والمثل القياسي، والتعبير الــمَثَلي، مع عرض شواهدها وتطبيقاتها من مدونة البحث، وكان أبرز ما خرج به من نتائج هي: ارتباط الأمثال بحياة العرب وعاداتهم وثقافاتهم، حتى أصبحت وثيقة تاريخية لما كانت عليه الحياة آنذاك. تبرز علاقة الحِجَاج بالمثل في أن الحِجَاج بالتمثيل يتأسس على نوع من المقارنة القائمة على التشبيه بين طرفين. الهدف الأسمى من الحِجَاج بالمثل هو إيصال الرسالة لحصول الإقناع والاقتناع. يعدُّ أكثم بن صيفي أبرز شخصية في العصر الجاهلي بما  يمتلكه من خبرات ورؤى  انعكست على الحياة العامة آنذاك. قيام الأمثال بأنواعها: المثل السائر، والمثل القياسي، والتعبير الــمَثَلي، بدورها الحِجَاجِي الإقناعي كما أراد قائلها. بروز دقة الفهم في أمثال أكثم، وحسن التهدي في النصح، رغبةً في تحقيق المراد. غالبًا ما يلجأ أكثم إلى أمثاله من خلال نظرة شاملة للحياة، وفاحصة للأحداث.   ABSTARCT :   THIS RESEARCH DISCUSSES THE PROVERB CONFUTATION OF AKTHAM IBN SAYFI ACROSS DIVIDING IT INTO TWO SECTIONS: THE FIRST INCLUDES THE THEORETICAL RESEARCH ASPECT, WHILE THE SECOND IS AN APPLIED STUDY OF THE PROVERB CONFUTATION OF AKTHAM IBN SAYFI. AFTER CLASSIFYINS IT INTO: PROVERB, ANALOGICAL PROVERB and PROVERBIAL EXPRESSION WITH THE EVIDENCES AND ITS APPLICATIONS FROM THE RESEARCH CORPUS. OF THE RESEARCH SIGNIFICANT FINDINGS ARE THE FOLLOWINGS: THE CONNECTION OF THE PROVERBS WITH THE ARABS LIFE, TRADITIONS AND CULTURES TO THE EXTENT THAT THEY BECOME A HISTORICAL DOCUMENT FOR THE LIFE AT THAT TIME. THE RELATION OF THE CONFUTATION WITH THE PROVERB APPEARS IN THAT CONFUTATION BY EXEMPLIFICATION IS FOUNDED ON A TYPE OF COMPARISON BASED ON COMPARISON OF SIMILA RITIES BETWEEN TWO ELEMENTS. THE ULTIMATE GOAL OF CONFWTATION BY EXEMPLIFICATION IS TO TRANSFER THE MESSAGE AIMING AT CONVINCING AND CONVENIENCE. AK THAM IBN SAYFI WAS A REMARKABLE CHARACTER IN THE JAHILI ERA, DUE TO HIS EXPERIENCES AND VISIONS CONVEYED IN LIFE AT THAT TIME. THE PROVERBS WITH THEIR DIFFERENT: MENTIONED TYPES  PLAY THEIR CONVENIENT CONFUTATIVE ROLE AS THEIR NARRATOR WISHED. THE ACCURATE COMPREHENSION IN AKTHAM’S PROVERBS BESIDE HIS GOOD GUIDANCE AND ADVICESE ARE VERY CLEAR IN SATISFYING THE PURPOSE. IN MOST, AKTHAM HAD  RESORTED TO MAKE HIS PROVERBS THROUGH A COMPREHEN SIVE VIEW TO LIFE AND TO INCIDENTS.